PELATIHAN PENGELOLAAN MATERI PEMBELAJARAN DENGAN E-LEARNING BAGI SEKOLAH MUHAMMADIYAH KECAMATAN MOYUDAN KABUPATEN SLEMAN - Winiarti, Sri; Astuti, Nur Rochmah Dyah Puji; Yuliansyah, Herman (Universitas Ahmad Dahlan, Yogyakarta, 2018)
The schools in Mayodan sub-district have not used information technology with maximum to support learning and education activity. They need assistance in community service to train them to organize learning media using eLearning. The methods of implementing the training are tutorial or assistance, giving a module to participants, workshop and evaluation process. The impact of this training is improvement knowledge in information technology uses. This impact can show from training result. The result showed 74% participants agree and like with this training results.